Double‐networks based on interconnected amphiphilic "in–out" star first polymer conetworks prepared by RAFT polymerization. Issue 19 (22nd October 2018) - Kitiri, Elina N.; Varnava, Constantina K.; Patrickios, Costas S.; Voutouri, Chrysovalantis; Stylianopoulos, Triantafyllos; Gradzielski, Michael; Hoffmann, Ingo
ABSTRACT: Double‐network hydrogels were prepared using well‐defined first networks comprising interconnected amphiphilic "in‐out" star copolymers synthesized via sequential reversible addition‐fragmentation chain transfer (RAFT) polymerization, and second networks based on a photopolymerized mixture of acrylamide and N, N ′‐methlyenebisacrylamide. All first and double‐network hydrogels were characterized in terms of their aqueous degrees of swelling and mechanical properties in compression. The most hydrophobic first and double‐network hydrogels exhibited the best mechanical properties, which may be attributed to their low aqueous swelling degrees and good mesoscale organization in water as revealed using small‐angle neutron scattering (SANS) which showed that the size of the formed hydrophobic domains could be controlled by the polymer conetwork structure. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 2161–2174 Abstract : Amphiphilic polymer conetworks based on interconnected "in‐out" star copolymers were synthesized using a four‐step sequential RAFT copolymerization, and were employed as scaffolds to prepare double‐network hydrogels which exhibited mechanical properties superior to their first network precursors.